RIFM fragrance ingredient safety assessment, p-isopropylbenzyl alcohol, CAS Registry Number 536-60-7. (15th July 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: Summary: The existing informati on supports the use of this material as described in this safety assessment . p- Isopropylbenzyl alcohol was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from the read-across analog benzyl alcohol (CAS # 100-51-6) show that p- isopropylbenzyl alcohol is not expected to be genotoxic. Data from the read-across analog benzyl alcohol (CAS # 100-51-6) provide a calculated MOE >100 for the repeated dose, developmental, and local respiratory toxicity endpoints. The reproductive toxicity endpoint was evaluated using the TTC for a Cramer Class I material, and the exposure is below the TTC (0.03 mg/kg/day). Data from read-across analog benzyl alcohol (CAS # 100-51-6) provided p- isopropylbenzyl alcohol a NESIL of 5900 μg/cm 2 for the skin sensitization endpoint. The phototoxicity and photoallergenicity endpoints were evaluated based on UV spectra; p- isopropylbenzyl alcohol is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; p- isopropylbenzyl alcohol was found not to be a PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC) are <1. Highlights: p- Isopropylbenzyl alcohol; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.